Breaking down linguistic barriers: The radical impact of translanguaging on pre-service EFL teachers' perspectives in Turkey. - Ömer Gökhan Ulum (PLoS ONE)
This study examines the perceptions and practices of translanguaging among pre-service English as a Foreign Language (EFL) teachers in Turkey, employing a mixed-method research design with a phenomenological framework. The sample consists of 401 pre-service EFL teachers from the Education Faculty's English Language Teaching (ELT) Department at a state university during the 2024-2025 academic year. Data collection included a rigorously developed 28-item Likert-scale questionnaire and semi-structured interviews. The questionnaire, refined through factor analysis, explored various dimensions of translanguaging, including its perceived benefits, challenges, and usage contexts. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined through thematic analysis. The results suggest that translanguaging is widely perceived as a valuable and natural pedagogical strategy, as it enhances learning by reducing language anxiety, fostering inclusivity, and promoting active participation. Its "natural" aspect lies in the alignment with learners' spontaneous use of their full linguistic repertoire, facilitating smoother integration into the learning process. Translanguaging is shown to alleviate anxiety, build confidence, and stimulate classroom engagement. This research underscores the significance of integrating translanguaging in teacher education programs and highlights the need for further investigation into its diverse effects on language learning and teaching practices.